Stevens–Johnson syndrome induced by toripalimab in a previously EGFR-TKI-treated advanced lung adenocarcinoma patient harboring EGFR mutations 19 del/T790M/C797S in trans and cis: a case report - Chen, Yang; Hong, Hanhan; Bao, Shujun; Tang, Hao (Frontiers in Pharmacology, 2023)
Background: The treatment paradigm for advanced non-small-cell lung cancer (NSCLC) is rapidly changing. Epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) and anti-programmed death-1 (PD-1) antibodies have increasingly been incorporated into routine care for nearly all patients with NSCLC. Toripalimab was recently approved as the first-line treatment for advanced non-squamous NSCLC in combination with chemotherapy. Stevens–Johnson syndrome (SJS) is a rare but potentially fatal complication of TKI and anti-PD-1 therapy. We reported a case of SJS after sequential use of EGFR-TKIs and toripalimab in an NSCLC patient with EGFR mutations 19 del/T790M/C797S in trans and cis. Case presentation: A 58-year-old man with stage IV NSCLC received gefitinib because next-generation sequencing (NGS) revealed an EGFR 19del, followed by osimertinib and pemetrexed with the emergence of EGFR T790M. Four EGFR mutations 19 del/T790M/C797S in trans and cis were detected after osimertinib resistance. The combination of toripalimab and docetaxel was administered as a third-line treatment. The patient developed SJS at 21 days, and toripalimab was discontinued. After treatment with methylprednisolone and prednisolone, the skin toxicity of the patient gradually decreased and eventually disappeared. The patient received osimertinib and anlotinib after recovery, and SJS has not recurred. The ongoing treatment is still effective and results in stable disease. Conclusion: We reported the first case of SJS induced by toripalimab in a patient with lung adenocarcinoma harboring multiple EGFR mutations. The TKI treatment after SJS was well tolerated and effective.